Analisis Prioritas Perbaikan Sistem Kerja Industri Rumah Tangga Dengan Program WISH - Dewi, Luciana Triani; Dewi K, Chandra (Universitas Katolik Parahyangan, 2015)
The purpose of this paper is to analyze work system improvements of home industries in Yogyakarta City,based on participatory ergonomics approach. WISH (Work Improvement for Safe Home) action checklisthas been used as the instrument to analyse and evaluate the working conditions. WISH programme isan action manual published by ILO (International Labour Organization) to improve work conditions ofhome manufacturing by using a participatory approach. The working conditions in WISH action checklistcovers five aspects; i.e. materials storage and handling, machine safety, work stations, physical environment,and welfare facilities and work organization. The early step in this study was identification of generalcharacteristics of home industries in Yogyakarta City. The results of identification were used as input indeveloping improvement actions. Analysis was done to determine the priority among all improvement aspectsand improvement actions based on WISH action checklist. The findings show the most priority aspect ofimprovement was Work Stations aspects with index priority 0.172. The action needed for the most priorityimprovement aspect was developed by consideration of home industries characteristics.